2021
DOI: 10.1155/2021/8894089
|View full text |Cite
|
Sign up to set email alerts
|

Human Intestinal Parasitic Infections: Prevalence and Associated Risk Factors among Elementary School Children in Merawi Town, Northwest Ethiopia

Abstract: Background. Intestinal parasitic infection is still common in Ethiopia. Periodic evaluation of the current status of human intestinal parasitic infections (HIPIs) is a prerequisite to controlling these health threats. This study is aimed at assessing the prevalence and determinant factors of HIPIs among elementary school-age children in Merawi town. Methods. A school-based cross-sectional study design was used among 403 children. The direct wet mount method was used to diagnose the stool samples. The sociodemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
2
4
0
2
Order By: Relevance
“…The result of this study was comparable with the number of studies reported in Ethiopia, such as Maksegnit (40.4%), Merawi Town (42.9%), Arbaminch (46.5%), 14 , 15 , 35 the pooled prevalence in Ethiopia (46.09%), 36 and Eritrea (45.3%). 23 In contrast, the current study prevalence was lower in comparison with studies done in various areas of the country, such as Mecha district (61.7%), Bahir Dar (52.4%), 9 , 19 and in other countries like Sudan (87.2%) 37 and Argentina (78.1%).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The result of this study was comparable with the number of studies reported in Ethiopia, such as Maksegnit (40.4%), Merawi Town (42.9%), Arbaminch (46.5%), 14 , 15 , 35 the pooled prevalence in Ethiopia (46.09%), 36 and Eritrea (45.3%). 23 In contrast, the current study prevalence was lower in comparison with studies done in various areas of the country, such as Mecha district (61.7%), Bahir Dar (52.4%), 9 , 19 and in other countries like Sudan (87.2%) 37 and Argentina (78.1%).…”
Section: Discussionsupporting
confidence: 88%
“…1,11 There are studies on intestinal parasites among school-age children in different areas of Ethiopia. [12][13][14][15] However, the major limitation of the studies was determining intestinal parasite prevalence by examination of a single stool specimen. In addition, opportunistic infections were not evaluated.…”
mentioning
confidence: 99%
“…The study was carried out in Imo State, south-eastern Nigeria (figure 1). Imo State lies within latitudes 4°45'N and 7°15'N, and longitudes 6°50'E and 7°25'E, with an area of about 5,100 km 2…”
Section: Study Areamentioning
confidence: 99%
“…Intestinal parasitic infections (intestinal worms) are major public health problems confronting the world, especially in developing countries [1]. IPIs have been identified as neglected tropical diseases (NTDs) [2][3][4] and have received global attention. Although IPIs affect all age groups, it is a major cause of morbidity among school-aged children [5] due to their unhygienic practices and weak immune system [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation